Disease-Modifying Therapies (DMTs) in Pregnant and Lactating Women with Multiple Sclerosis: Analysis of Real-World Data from EudraVigilance Database - Liberata Sportiello; Raffaella Di Napoli; Nunzia Balzano; Annamaria Mascolo; Rosanna Ruggiero; Luigi Di Costanzo; Davida Monaco; Giorgia Teresa Maniscalco; Annalisa Capuano (MDPI AG, 2023)
(1) Background: The purpose of study was to compare the safety profile of glatiramer with natalizumab, alemtuzumab and ocrelizumab in pregnant and lactating women affected by multiple sclerosis (MS). (2) Methods: Individual case safety reports (ICSRs) were retrieved from the European spontaneous reporting system database (EudraVigilance). The reporting odds ratios (RORs) were computed to compare the reporting probability of events between natalizumab, alemtuzumab and ocrelizumab vs. glatiramer. (3) Results: A total of 1236 ICSRs reporting at least one DMT as a suspected drug were selected. More adverse drug reactions (ADRs) unrelated to pregnancy and breastfeeding (n = 1171; 32.6%) were reported than ADRs specific to pregnancy and breastfeeding (n = 1093; 30.4%). The most frequently reported unrelated ADR was MS relapse. Alemtuzumab and natalizumab seem to have a lower reporting probability of MS relapse compared to glatiramer (ROR 0.17, 95% CI 0.07-0.45 and ROR 0.34, 95% CI 0.20-0.57). Among pregnancy- and breastfeeding-related ADRs, the first most reported event was spontaneous abortion (n = 321; 8.9%). Natalizumab and ocrelizumab were associated with a higher reporting probability of spontaneous abortion compared to glatiramer (ROR 2.22, 95% CI 1.58-3.12; ROR 2.18, 95% CI 1.34-3.54, respectively), while alemtuzumab had a lower reporting frequency (ROR 0.32, 95% CI 0.17-0.60). (4) Conclusions: This study did not suggest any strong or new insights for DMTs in this special subpopulation. However, further studies need to be performed.